c.1 - Jomo, K.S. (ed.); Baudot, Jacques (ed.) (Hyderabad, 2007)
Many mainstream economists have claimed that globalization creates worldwide growth, and that economic liberalization will lead to the economic convergence and lower inequality. It is now clear that since the 1980$1 (Bs the world economy has experienced slower growth as well as greater inequalities at the national level. The research in this volume provides rigorous empirical analyses of how economic liberalization has actually affected inequality, poverty and development in recent decades. Avoiding polemics and rhetoric, the book provides a balanced account of recent trends, the effect of globalization and liberalization, and the comparative experiences of countries that have pursued different economic policies and trajectories.s
Keywords: Poverty